2020
DOI: 10.21203/rs.2.20728/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Health Information Seeking Behavior of Breast Cancer Patients: A Qualitative Study

Abstract: Background: Breast cancer is the most common cancer of women worldwide. This study was aimed to review systematically the current literature on the health information seeking behavior of breast cancer patients and to conduct the qualitative analysis of findings. Methods: We searched PubMed, Web of Science, Science Direct, CINHAL, Embase, Google Scholar, Cochrane database of systematic review, PSYCINO, SID and Magiran databases. A total of 60 articles included in the study. Findings of all studies were extracte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 49 publications
(246 reference statements)
0
3
0
Order By: Relevance
“…For data collection purposes, a team consisting of three female academics developed a structured interview guide based on an extensive review of relevant literature. [14][15][16][17]18,23,30,[33][34][35][36] The reason for selecting the focus group method was its ability to gather information, facilitate comparison and contrast of ideas, and encourage participants to generate ideas. These benefits aligned with the goals of our study.…”
Section: Data Collectionmentioning
confidence: 99%
“…For data collection purposes, a team consisting of three female academics developed a structured interview guide based on an extensive review of relevant literature. [14][15][16][17]18,23,30,[33][34][35][36] The reason for selecting the focus group method was its ability to gather information, facilitate comparison and contrast of ideas, and encourage participants to generate ideas. These benefits aligned with the goals of our study.…”
Section: Data Collectionmentioning
confidence: 99%
“…Davinia et al, in an assessment of patients with MBC in their first year after diagnosis found that most participants had high informational needs, and were most interested in information about treatment and disease [11]. In a systematic review of studies on health information seeking behaviour of breast cancer patients, Ravangard found a high level of unmet informational needs, and also a high degree of dissatisfaction with information provided by care providers [12]. Other studies have repeatedly demonstrated the needs for information among BC patients across their cancer journey and even as survivors [13] [14] [15], and others have shown association between having informational needs met and satisfaction with care [16].…”
Section: Themesmentioning
confidence: 99%
“…Information is communicative meaningful symbols transferred between two points. Information‐seeking behaviour can be classified as either proactive seeking of information, passive exposure to information, or behaviour aimed at avoiding information (Ravangard et al, 2020). Health information‐seeking behaviour is a complex concept that enables individuals to deal with improving health and engaging with the details of a medical condition or the psychological consequences of the diagnosis (Zimmerman & Shaw, 2020).…”
Section: Introductionmentioning
confidence: 99%